Association study of polymorphisms in miRNAs with T2DM in Chinese population - Li, Yiping (Int J Med Sci, 2015)
Accumulated evidence indicates that microRNA (miRNA or miR) is involved in the development of type 2 diabetes (T2DM). Several studies have shown that single nucleotide polymorphisms (SNPs) located in miRNAs are associated with T2DM in Caucasian populations. The association studies of miRNA's SNPs with T2DM in Asian are rarely reported, and there are distinct genetic differences between Caucasian and Asian populations. The focus of this study, therefore, is the association of T2DM with five SNPs (rs895819 in miR-27a, rs531564 in miR-124a, rs11888095 in miR-128a, rs3820455 in miR-194a and rs2910164 in miR-146a) located in five miRNAs in a Han Chinese population. A total of 738 subjects with T2DM and 610 non-diabetic subjects were genotyped using the TaqMan method. Next, the associations between the five SNPs with T2DM and individual metabolic traits were evaluated. Our data showed that the C allele of rs531564 in miR-124a may protect against T2DM (P=0.009, OR=0.758; 95%CI: 0.616-0.933). Conversely, the C allele of rs2910164 in miR-146a may increase the risk of developing T2DM (P<0.001, OR=1.459; 95%CI: 1.244-1.712). However, these five SNPs did not exhibit significant associations with individual metabolic traits in either the T2DM or non-diabetic groups. Our results revealed that genetic variations in miRNAs were associated with T2DM susceptibility in a Han Chinese population, and these results highlight the need to study the functional effects of these variants in miRNAs on the risk of developing T2DM.